Regulation of butyrate-induced resistance through ampk signaling pathway in human colon cancer cells - Yoo, Hee Young; Park, So Yeon; Chang, Sun Young; Kim, So Hee (Biomedicines, 2021)
Butyrates inhibit cell growth in colon cancer cells by inhibiting histone deacetylases. However, chronic exposure to butyrates induces butyrate resistance in colon cancer cells. The mechanism underlying the acquisition of resistance is not yet fully understood. Here, butyrateresistant (BR) colon cancer cells were developed in HCT116, HT29, and SW480 human colon cancer cells and were confirmed by the increase in the inhibitory concentrations of cell growth by 50% (IC50 ) compared to their respective parental (PT) cells. Chronic exposure to butyrate induced autophagy via higher expression of Beclin-1 and LC3B-II. The AMP-activated protein kinase (AMPK) was downregulated along with the activation of Akt and mammalian target of rapamycin (mTOR) and decrease in acetyl-CoA carboxylase (ACC) in BR colon cancer cells compared to those in their respective PT cells. Activation of AMPK by AICAR treatment in BR colon cancer cells suppressed cell proliferation by inhibiting Akt and mTOR and activating ACC. Taken together, chronic exposure to butyrate increased butyrate resistance in human colon cancer by inducing protective autophagy through the downregulation of AMPK/ACC and activation of Akt/mTOR signaling. Activation of AMPK restored sensitivity to butyrate by the inhibition of Akt/mTOR, suggesting that AMPK could be a therapeutic target for BR colon cancers.
Keywords: ACC; Akt; AMPK; Autophagy; Butyrate resistance; Colon cancer; MTOR